First report of the lace bug Neoplerochila paliatseasi (Rodrigues, 1981) (Hemiptera: Tingidae) infesting cultivated olive trees in South Africa, and its complete mitochondrial sequence - Langley, Jethro; Cornwall, Morgan; Powell, Chanté; Costa, Carlo; Allsopp, Elleunorah; Noort, Simon Van; Guilbert, Eric; Asch, Barbara Van (Zootaxa, 2020)
Olive lace bugs are small phytophagous Hemipteran insects known to cause agricultural losses in olive production in South Africa. Plerochila australis (Distant, 1904) has been reported as the species responsible for damage to olive trees; however, the diversity of olive lace bug species in the region has lacked attention. Adult olive lace bugs were collected incidentally from wild and cultivated olive trees in the Western Cape Province, and identified as P. australis and Neoplerochila paliatseasi (Rodrigues, 1981). The complete mitochondrial genome of a representative specimen of N. paliatseasi was sequenced, and used for comparative mitogenomics and phylogenetic reconstruction within the family. Furthermore, the value of DNA barcodes for species identification in Tingidae was assessed using genetic clustering and estimates of genetic divergence. The patterns of genetic clustering and genetic divergence of COI sequences supported the morphological identification of N. paliatseasi, and the utility of DNA barcoding methods in Tingidae. The complete mitogenome sequence had the typical Metazoan gene content and order, including 13 PCGs, 22 tRNAs, two rRNAs, and an AT-rich non-coding region. A+T content was high, as commonly found in Tingidae. The phylogenetic reconstruction recovered Agramma hupehanum (Drake & Maa 1954) as basal to Tingini, and as a sister species to N. paliatseasi. Stephanitis Stål 1873 and Corythucha Stål 1873 were monophyletic, but Metasalis populi (Takeya 1932) was not recovered as sister to Tingis cardui (Linnaeus 1746), as expected. The mitochondrial phylogeny of the family Tingidae has been recovered inconsistently across different studies, possibly due to sequence heterogeneity and high mutation rates. Species diversity of olive lace bugs in South Africa was previously underestimated. The presence of P. australis was confirmed in both wild and cultivated olives, and N. paliatseasi is reported in cultivated olives for the first time. These results warrant further investigation on the diversity and distribution of olive lace bugs in the Western Cape to inform pest control strategies.